2018
DOI: 10.1080/09540121.2018.1510101
|View full text |Cite
|
Sign up to set email alerts
|

HIV care continuum outcomes of pregnant women living with HIV with and without depression

Abstract: Women living with HIV (WLWH) suffer from poor viral suppression and retention postpartum. The effect of perinatal depression on care continuum outcomes during pregnancy and postpartum is unknown. We performed a retrospective cohort analysis using HIV surveillance data of pregnant WLWH enrolled in perinatal case management in Philadelphia and evaluated the association between possible or definite depression with four outcomes: viral suppression at delivery, care engagement within three months postpartum, retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…It is estimated that more than 60% and 40% of people living with HIV in China exhibited symptoms of depression and anxiety respectively . Moreover, depression and anxiety have been linked to suboptimal HIV treatment outcomes, worse quality of life and increased mortality .…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that more than 60% and 40% of people living with HIV in China exhibited symptoms of depression and anxiety respectively . Moreover, depression and anxiety have been linked to suboptimal HIV treatment outcomes, worse quality of life and increased mortality .…”
Section: Introductionmentioning
confidence: 99%
“…Almost one in four PLWH experienced moderate to severe symptoms of depression [ 21 , 22 ]. Although certain studies found no observed associations found between depression and self-reported adherence [ 21 ] or no direct association between depression and VLS [ 19 , 23 ]. PLWH with recent onset depression were less likely to reach VLS and had increased mortality [ 21 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies also suggest that changes in the severity of depressive symptoms may be more specifically related to social determinants of health than the patient-provider relationship for PLWH [ 23 , 25 30 ]. Multiple social determinants of health such as lower income level, transactional sex, housing instability, long-term survivor status, low social support (perceived or real), poor educational attainment, and food insecurity were shown to be associated with a higher prevalence of depressive symptoms [ 23 , 25 30 ]. Although the patient–provider relationship was beneficial for mental health outcomes in PLWH, addressing sociodemographic factors may be of greater importance [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study examines the overall impact of depressive symptoms on VS throughout the perinatal period and the extent to which this association is mediated by ART adherence among pregnant women with HIV. Prior studies examining these associations were often exploratory analyses of small cross-sectional samples, usually lacking the longitudinal perspective of how these important variables change over the perinatal period [ 9 , 10 , 39 ]. Gaining such understanding is important as effective interventions to improve ART adherence and VS for women with HIV in the perinatal period continue to be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the majority of studies examining the association between perinatal depression and VS were conducted outside the United States [ 6–8 ] where antiretroviral therapy (ART) is not as readily available and contextual factors differ from those in the United States. Studies from the United States have been cross-sectional and have found inconsistent associations between perinatal depression, ART adherence, and VS [ 9 , 10 ].…”
mentioning
confidence: 99%